2013
DOI: 10.1007/s13277-013-0658-6
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA: an emerging paradigm of cancer research

Abstract: Recent studies have demonstrated the importance of non-protein coding part of human genome in carcinogenesis and metastasis. Among numerous kinds of non-protein coding RNAs, long noncoding RNAs (lncRNAs) play a key regulatory role in cancer biology. LncRNAs are dysregulated in different kinds of cancer and the expression levels of certain lncRNAs are associated with recurrence, metastasis, and prognosis of cancer. It is also proved that overexpression of certain lncRNAs, behaving like oncogenes, can promote ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
286
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(289 citation statements)
references
References 63 publications
2
286
0
1
Order By: Relevance
“…Moreover, lncRNAs seemed to penetrate into all aspects of gene regulation, including epigenetic inheritance, transcription, post‐transcription and translation 38, 39. Interestingly, Jun Huang et al40 reported that lncRNA MALAT1 mediated autophagy of retinoblastoma cells through acting on miR‐124.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, lncRNAs seemed to penetrate into all aspects of gene regulation, including epigenetic inheritance, transcription, post‐transcription and translation 38, 39. Interestingly, Jun Huang et al40 reported that lncRNA MALAT1 mediated autophagy of retinoblastoma cells through acting on miR‐124.…”
Section: Discussionmentioning
confidence: 99%
“…It is increasingly recognized that lncRNAs constitute an important component in the regulation of gene expression and carcinogenesis. 9,24 Long noncoding RNAs are dysregulated in different kinds of cancer, demonstrating both oncogenic and tumor-suppressive roles, thus suggesting that their aberrant expression may contribute substantially to cancer development. 11 However, the biological functions of the vast majority of lncRNAs remain unknown.…”
mentioning
confidence: 99%
“…Therefore, biomarkers to indicate morbidity associated with gastric cancer are required, particularly for use among populations with a high prevalence of disease. A previous study demonstrated that lncRNAs may function as a novel class of diagnostic and treatment indicators of several types of cancer (8). However, the role of lncRNA expression in gastric cancer remains largely unstudied.…”
Section: A B Discussionmentioning
confidence: 99%
“…An increasing number of studies have focused on lncRNAs, which have been demonstrated to contribute to the onset and progression of numerous diseases (7). Functional analyses have indicated that lncRNAs are involved in the regulation of a large number of biological processes, including cancer development and progression (8,9). Expression of the lncRNA, HOTAIR, has been correlated with tumor metastasis and poor prognosis in hepatocellular (10), pancreatic (11), breast (12) and colorectal cancer (13), and gastrointestinal stromal tumors (14).…”
Section: Introductionmentioning
confidence: 99%